2007
DOI: 10.1016/j.jbiomech.2006.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical strain regulates TNFR2 but not TNFR1 in TMJ cells

Abstract: We sought to examine whether cyclic tensile strain (CTS) regulates the gene expression of tumor necrosis factor (TNF)-alpha, its receptors TNFR1 and TNFR2, and inducible nitric oxide synthase (iNOS) under inflammatory conditions, and whether these effects of CTS are sustained. Rat temporomandibular joint disc cells (TDC) were exposed to CTS in the presence or absence of interleukin (IL)-1beta for 4 and 24 h. Cells were also stimulated with IL-1beta for 24 h while being subjected to CTS only for the initial 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In particular, low-level strain has generally been observed to block the expression of inflammation-related genes that augment cartilage destruction. 87 , 132 , 134 , 137 , 142 , 147 , 149 , 150 For example, using high frequency and low strain (3% elongation at 25 MHz), IL1 pro-inflammatory activity was inhibited, due to block of IL1-mediated NF-κB nuclear translocation, 134 in a transforming growth factor-β-activated kinase-1 (TAK1)-dependent fashion. 156 This prevented subsequent transcription of inflammatory gene targets, which normally result from NF-κB activation.…”
Section: Effect Of Mechanical Strain On Cartilage Cellsmentioning
confidence: 99%
“…In particular, low-level strain has generally been observed to block the expression of inflammation-related genes that augment cartilage destruction. 87 , 132 , 134 , 137 , 142 , 147 , 149 , 150 For example, using high frequency and low strain (3% elongation at 25 MHz), IL1 pro-inflammatory activity was inhibited, due to block of IL1-mediated NF-κB nuclear translocation, 134 in a transforming growth factor-β-activated kinase-1 (TAK1)-dependent fashion. 156 This prevented subsequent transcription of inflammatory gene targets, which normally result from NF-κB activation.…”
Section: Effect Of Mechanical Strain On Cartilage Cellsmentioning
confidence: 99%
“…While different these cell-based configurations can help explain possible inhibitory mechanisms when loading intact cartilage using our METS. Agarwal et al16,1921,39 reported that tensile strain (3%, 20%) inhibited or reduced IL-1-induced increases in gene expression (mRNA) for nitric oxide (NO), inducible nitric oxide synthase (iNOS), tumor necrosis factor (TNF)-α, cyclo-oxygenase (COX)-2, and MMP-3, 7, 8, 9, 13, 16, 17 and 19, had no affect on MMP-2, 11 and 14 and TIMP-1, 2 and 3, and reversed IL-1 inhibition of aggrecan synthesis. They concluded that the tensile strain acts at multiple sites within the NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Based on another research conducted on rat TMJ disc cells, which was exposed to cyclic tensile strain, it was found that the expression of TNFR2 was regulated by biomechanical signals regulate. However, this regulation did not occur to TNFR1 under inflammatory conditions [122].…”
Section: Tnf-tnfrs Interactions In Tmdsmentioning
confidence: 80%